Chinese International Students in the United States: The Interplay of Students’ Acculturative Stress, Academic Standing, and Quality of Life - Su, Zhaohui; McDonnell, Dean; Shi, Feng; Liang, Bin; Li, Xiaoshan; Wen, Jun; Cai, Yuyang; Xiang, Yu-Tao; Yang, Ling (Frontiers in Psychology, 2021)
Background: Acculturative stress negatively shapes international students’ physical and psychological health and wellbeing. While useful insights are available, little is known about how acculturative stress affects international students’ quality of life or how students’ academic experience might be a protective factor against their acculturative stress, particularly among Chinese international students. Chinese international students are the largest body of international students studying in the United States (U.S.)— A deep understanding of Chinese international students’ acculturative stress could shed light on other students’ studying aboard experience as well. Therefore, to bridge the research gap, we aim to examine the interplay between international students’ school classification, acculturative stress, and quality of life in a geographically representative sample of Chinese international students studying in the U.S. Methods: An online survey was developed and distributed to approximately 220 higher education institutions across the U.S., including public universities, private universities, and community colleges. The International student offices and Chinese student associations supported the survey distribution. No force-response mechanism was integrated into the survey questionnaire; among all 2,321 international students who participated in the survey, 751 students provided complete responses. Results: Findings suggest that acculturative stress negatively affects all four domains of Chinese international students’ quality of life, irrespective of their school classification. Results also indicate that compared to master’s and doctoral students, undergraduates experience the highest levels of acculturative stress. Furthermore, a significant difference emerged in undergraduate and doctoral international students’ acculturative stress levels, but not among undergraduate and master’s students. Conclusions: Findings of our study show that while acculturative stress deteriorates international students’ quality of life, students’ academic experience may serve as a protective factor in the equation—undergraduates were found to have greater acculturative stress, and that greater levels of acculturative stress were associated with lower levels of quality of life. Overall, results of this study can inform the design of interventions to alleviate international students’ acculturative stress, such as programs tailored to students’ academic experience (e.g., school classification). Future research could further examine ways to mitigate, if not eliminate, international students’ acculturative stress to safeguard these students’ wellbeing and quality of life.